DAMPAK PENGGUNAAN SMART PHONE TERHADAP PERILAKU SOSIAL SISWA - Arrahma, Al Bunia; Balqis, Humairah; Ali, Azwan; Marisa, Siti; Gunawan, Gunawan (Atthiflah: Journal of Early Childhood Islamic Education, 2024)
Cell phones and smartphones can have a positive impact if used wisely and permanently, but can also have a negative impact if used incorrectly. Smartphone addiction is a behavior where people rely on their smartphones for daily activities and lack self-control, giving the impression that users are being deceived by the presence of smartphones and applications that provide greater convenience and supervision must be carried out to overcome interaction problems between students and prevent possible negative impacts. caused by excessive use of smartphones in the school environment. Keywords need to be included to describe the realm of the problem under study and the main terms that underlie the implementation of the study. Keywords can be single words or compound words. The number of keywords is around 3-5 words. These keywords are needed for computerization. Searching for research titles and abstracts is made easy with these keywords